2022
DOI: 10.1177/17534259221094559
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid inhibits Th17 cell differentiation via STAT3/RORγt pathway and suppresses Schwann cell-mediated Th17 cell migration by reducing CXCL9/10 expression

Abstract: Th17 cells represent important immune cells. Ursolic acid (UA) can regulate immune cell activities. This study was aimed to explore the effects of UA on Th17 cell differentiation and Schwann cell(SCs)-mediated migration and the potential mechanism. Naïve CD4+ T cells were isolated from rat peripheral blood, induced for Th17 cell differentiation, and treated with UA. The proportion of Th17 cells was detected by flow cytometry assay. SCs were co-cultured with Th17 cells. Th17 cell migration was detected by Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…And small molecules targeting T-bet and RORγt also inhibit EAE (35). UA could reduce the serum levels of IL-6, IFN-γ, TNF-α and IL-17 (22,24,48). In the present study, UAOS-Na-treated EAE mice showed a significant reduction in serum levels of IFN-γ, TNF-α, IL-6, and IL-17A and in expression of key transcription factors T-bet and ROR-γt in spinal cord.…”
Section: Discussionsupporting
confidence: 57%
“…And small molecules targeting T-bet and RORγt also inhibit EAE (35). UA could reduce the serum levels of IL-6, IFN-γ, TNF-α and IL-17 (22,24,48). In the present study, UAOS-Na-treated EAE mice showed a significant reduction in serum levels of IFN-γ, TNF-α, IL-6, and IL-17A and in expression of key transcription factors T-bet and ROR-γt in spinal cord.…”
Section: Discussionsupporting
confidence: 57%
“…When cytokines, such as IL-6, IL-19, and IL-22, bind to their receptors, JAK is phosphorylated and binds to the cytokine receptor to make a receptor complex, resulting in the phosphorylation of downstream STAT3 at Tyr705 and Ser727, and the phospho-STAT3 meet to form dimers. These dimers bind to the nuclear DNA and regulate the expression of inflammatory proteins [ 44 , 45 ]. Western blotting showed that the expression levels of LPS-induced p-JAK1 and p-STAT3 were drastically reduced following FFE application ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%